2021
DOI: 10.1186/s12891-021-04735-2
|View full text |Cite
|
Sign up to set email alerts
|

Defining matrix Gla protein expression in the Dunkin-Hartley guinea pig model of spontaneous osteoarthritis

Abstract: Background Matrix Gla (γ-carboxyglutamate) protein (MGP) is considered a strong inhibitor of ectopic calcification, and it has been associated with OA severity, although not conclusively. We utilized male Dunkin-Hartley (DH) guinea pigs to investigate the expression of MGP throughout aging and disease pathogenesis in a spontaneous model. Method Twenty-five male DH guinea pigs were obtained and nurtured to several timepoints, and then randomly and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The pathogenesis of OA has not yet been fully elucidated, as it is a multifactorial process. Previous studies of our research team mainly focused on protein-coding genes in OA [ 147 , 148 ]; however, we found that recent studies on its pathogenesis have shifted focus to the roles of noncoding RNAs by literature search. Therefore, we summarized the lncRNAs that play a role in osteoarthritic cartilage in this review.…”
Section: Discussionmentioning
confidence: 96%
“…The pathogenesis of OA has not yet been fully elucidated, as it is a multifactorial process. Previous studies of our research team mainly focused on protein-coding genes in OA [ 147 , 148 ]; however, we found that recent studies on its pathogenesis have shifted focus to the roles of noncoding RNAs by literature search. Therefore, we summarized the lncRNAs that play a role in osteoarthritic cartilage in this review.…”
Section: Discussionmentioning
confidence: 96%
“…At 12 months, the surface was eroded until complete cartilage loss at 15 months [16][17][18][19]. OARSI and Mankin scores worsened with aging, as well as CT, instantaneous modulus, cellularity, matrix integrity, insulin growth factor 1 (IGF1), and receptor activator of nuclear factor kappa-B ligand (RANKL) [20][21][22][23]. During aging, as regards SB, an increase in Tb.Th and osteoprotegerin (OPG) and a decrease in bone volume/tissue volume (BV/TV), trabecular bone pattern factor (Tb.Pf), and structure model index (SMI) were observed [17,18,20].…”
Section: Naturally Occurring Oa In Guinea Pigsmentioning
confidence: 99%